A lithium‐organic framework as a fluorescent sensor for detecting aluminum (III) ion. (18th June 2019) - Feng, Lijuan; Ren, Guojian; Ding, Shunan; Wang, Fuxiang; Yang, Weiting; Liang, Zhiqiang; Pan, Qinhe
Abstract : Due to the low coordination number and the relatively weak coordination ability, it is a great challenge to introduce Li + into the construction of metal–organic frameworks (MOFs). Here, one Li‐based metal–organic framework (Li‐MOF), [Li4 L(DMF)2 ]n (HNU‐31 ), is constructed by the assembly of LiNO3 and 5‐(bis(4‐carboxybenzyl)amino)isophthalic acid (H4 L) ligand, which possesses a 3D framework, and can be serve as a luminescent sensor for detecting Al 3+ ion with the detection limit of 4 × 10 −6  M. Abstract : A Li‐based MOF is constructed, which possesses a 3D framework, and can be serve as a luminescent sensor for detecting Al 3+ ion with the detection limit of 4 × 10 −6  M.